Phytochemical Characterization Of Vernonia Amygdalina.Del Ethanolic Extract Fraction And Contractile Response On Isolated Uterine Tissue In Female Albino Wistar Rats - Igwe, K.K..; S.M Anika, I..I.Ijeh P..N. Okafor (International Journal of Scientific Research and Management (IJSRM), 2015)
The aim of the research is to analyze the phytocomponent in the contractile fraction of Vernonia amygdalina on uterus using GC-MS analysis. In the present research, extract for leaf of Vernonia amygdalina was screened for contractile potential by standard test procedures and this study was further extended by fractionation and analyzing the potent bioactive compounds in the ethanolic extract fraction of Vernonia amygdalina leaves using GC-MS analysis. Using physiograph uterine tissue contractile amplitudes were determined at 0.25 mg/ml, 0.3 mg/ml, 0.7 mg/ml, 1.0mg/ml, 1.25mg/ml and 1.5mg/ml for the different fractions. Fraction F5 had the best contractile response on isolated uterine tissue in the presence of agonist acetylcholine (ACh). F5 was used for characterization by GCMS analysis. In the quantitative phytochemical characterization using various extracts of the plant, it was found that most of the biologically active phytochemicals were present in the ethanolic extract of Vernonia amygdalina leaves. Gas Chromatography-Mass Spectrometry (GC-MS) of F5 revealed the presence of eleven bioactive compounds which includes, 3, 5-bis 1, 1 dimethylethyl (Phenol) ; Tetradecanoic acid ; 1, 2- epoxyhexadecane(Oxirane) ; Methylhexadecanoate (Palmitic acid) ; Hexadecanoic acid (Eicosanoic acid); 9, 12-octadecadienoic acid (Linoleic acid); 3, 7-dimethyldodecan-1-ol (Phytol) ; 6-octadecenoic acid(Oleic acid); octadecanoic acid(Stearic acid); Cholest-5, 3-ol, 5-acetate (Cholestane) and 1,2-Benzenedicarboxylic acid (Di-n-octyl phthalate). Results confirmed the presence of contractile potent compounds in the leaf extract of Vernonia amygdalina